Identifikasi longsoran bawah laut berdasarkan penafsiran seismik pantul di perairan Flores - Budiono, Kris (Indonesian Journal on Geoscience, 2009)
http://dx.doi.org/10.17014/ijog.vol4no1.20092Submarine sliding frequently cause tsunami or a high velocity big wave around the submarine slid- ing area which enable to reach a long distance. This sliding is not always as a causal factor for hazard and even associate with storm and earthquake. Some of them occur in a narrow area and itâs just formed due to gravitational movement. Different with mechanism of landslide, which is commonly due to water saturated soil, the submarine sliding is a more complex event. The submarine sliding is an important natural process which causes a big volume of sediment mass moves from a shallow area to a much deeper area of seafloor. There are many types and causal factors of seafloor instability, but the sliding terminology is predominantly used for the phenomena. A variety of seafloor materials, environments and sediment masses are some extreme influential factors in creat- ing the types of submarine sliding. The reflector of seismics is usefull to interpret the indications of the occurrence of geological structure and sub-marine slumping In case of the Flores Sea, earthquake is a major causal factor for creating submarine sliding. The bigger magnitude of earthquake, the greater the dimension of submarine sliding. Eventually, it may affect to the more possible occurrence of a potential hazardous tsunami. Â